The Paperbark Shoe - Goldbloom, Goldie (Australia Frementle Press, 2010)
Gin, the albino, marries to escape the confines of an asylum. Toad, a little man who wears corsets, marries to prove his manhood. Together they are freaks - feared and ridiculed by the remote farming community in which they live.
Keywords: Prisoners of war -- Italians -- Australia